2004
DOI: 10.1086/422842
|View full text |Cite
|
Sign up to set email alerts
|

The Ultraluminous X‐Ray Source Population from the Chandra Archive of Galaxies

Abstract: One hundred fifty-four discrete non-nuclear ultraluminous X-ray ( ULX) sources, with spectroscopically determined intrinsic X-ray luminosities greater than 10 39 ergs s À1 , are identified in 82 galaxies observed with Chandra's Advanced CCD Imaging Spectrometer. Source positions, X-ray luminosities, and spectral and timing characteristics are tabulated. Statistical comparisons between these X-ray properties and those of the weaker discrete sources in the same fields (mainly neutron star and stellar-mass black … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
281
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(305 citation statements)
references
References 123 publications
24
281
0
Order By: Relevance
“…X-ray binaries and other luminous objects that could also be observed at these redshifts (e.g. Swartz et al 2004;Feng & Soria 2011). These sources may also show beamed luminosities comparable to the fainter blazars, but whose intrinsic luminosity generally is found at around 10 38 erg s´1.…”
Section: Rgmentioning
confidence: 96%
“…X-ray binaries and other luminous objects that could also be observed at these redshifts (e.g. Swartz et al 2004;Feng & Soria 2011). These sources may also show beamed luminosities comparable to the fainter blazars, but whose intrinsic luminosity generally is found at around 10 38 erg s´1.…”
Section: Rgmentioning
confidence: 96%
“…However, Swartz et al (2004) found that the average slopes of X-ray binaries in nearby galaxies are Γ = 1.88 ± 0.06 (1.97 ± 0.11) for binaries with luminosity larger (smaller) than 10 39 erg s −1 , respectively. Only 7% (8%) of the binaries studied by Swartz et al (2004) have slopes Γ ≤ 1.4.…”
Section: Hardness Ratiomentioning
confidence: 97%
“…Harder spectra are sometimes indeed found in galaxies (e.g., see the slopes for single power-law fits in Dahlem et al 1998) where they can result from bright X-ray binaries (Persic & Rephaeli 2002). However, Swartz et al (2004) found that the average slopes of X-ray binaries in nearby galaxies are Γ = 1.88 ± 0.06 (1.97 ± 0.11) for binaries with luminosity larger (smaller) than 10 39 erg s −1 , respectively. Only 7% (8%) of the binaries studied by Swartz et al (2004) have slopes Γ ≤ 1.4.…”
Section: Hardness Ratiomentioning
confidence: 99%
“…Two arguments stand out as the principle reasons the ULX population is not dominated by (large) accreting IMBHs. Firstly, the luminosity function of X-ray sources in galaxies (XLF) has an unbroken power-law form for 5 decades up to a luminosity of ∼ 2 × 10 40 erg s −1 (Grimm, Gilfanov & Sunyaev 2003;Swartz et al 2004). This break occurs at ∼ 10 per cent of the Eddington luminosity for the ∼ 1000M ⊙ black holes inferred from ULX spectroscopy.…”
Section: The Problem(s) With Imbhsmentioning
confidence: 99%
“…Unfortunately, ULXs do not generally show much short-term variability (Swartz et al 2004), with very few examples displaying sufficient variability power to establish a PSD from (Feng & Kaaret 2005). However, some measurements have been made.…”
Section: Power Spectral Densities For Ulxsmentioning
confidence: 99%